2021
DOI: 10.1007/s12571-021-01182-8
|View full text |Cite
|
Sign up to set email alerts
|

Urbanisation as driver of food system transformation and opportunities for rural livelihoods

Abstract: Urbanisation is changing food systems globally, and in particular in sub-Saharan Africa and South Asia. This transformation can affect rural livelihoods in multiple ways. Evidence on what enabling conditions are needed to materialise the opportunities and limit risks is scattered. Here we review scientific literature to elaborate on how urbanisation affects food systems, and on the enabling conditions that subsequently shape opportunities for rural livelihoods. We find that urbanisation leads to a rising and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 129 publications
2
44
0
Order By: Relevance
“…We found that all but 0.8% of the farmers who used fertilizer used mineral fertilizer on their farms, which corresponded to findings by Bon et al [78]. This widespread adoption of fertilizers might be facilitated by several 'enabling conditions' associated with urbanization that spill over to the more rural hinterlands of cities [83]. In our sample, the average SSI takes a value of 0.71 (Table 3), which implies that the majority of farmers lived in the more rural hinterlands of the study area rather than in the urban neighborhoods at the fringe of the city.…”
Section: Mineral Fertilizer and Fymsupporting
confidence: 88%
See 2 more Smart Citations
“…We found that all but 0.8% of the farmers who used fertilizer used mineral fertilizer on their farms, which corresponded to findings by Bon et al [78]. This widespread adoption of fertilizers might be facilitated by several 'enabling conditions' associated with urbanization that spill over to the more rural hinterlands of cities [83]. In our sample, the average SSI takes a value of 0.71 (Table 3), which implies that the majority of farmers lived in the more rural hinterlands of the study area rather than in the urban neighborhoods at the fringe of the city.…”
Section: Mineral Fertilizer and Fymsupporting
confidence: 88%
“…This could be facilitated by the relative proximity to Bangalore and related access to road, transportation, and market infrastructures. Information and knowledge exchanges (e.g., extension services and mobile phones), as well as other institutional conditions might also enable adoption [83]. Besides proximity to the city of Bangalore, several secondary towns along the two study transects (see the map in Figure A1) might provide access to farm inputs and agricultural markets where farmers could also sell their crops [83].…”
Section: Mineral Fertilizer and Fymmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest differential drivers—and potential levers for action—for unprocessed versus processed meats, with urbanisation having less influence on processed meat consumption compared with socioeconomic factors. 44 , 45 This factor is an important consideration for influencing total meat consumption globally, given the generally stronger links with NCDs of processed meats.…”
Section: Discussionmentioning
confidence: 99%
“…Food demand is likely to increase, and changes in what food is in demand can be expected. Furthermore, market linkages and changes in land-use dynamics will also be influenced [38]. The extent to which these changes contribute to or undermine sustainability and resilience is neither predetermined nor fixed.…”
Section: Population Dynamicsmentioning
confidence: 99%